PENINGKATAN PROFESIONALITAS KINERJA APARATUR SIPIL NEGARA (ASN) DI BADAN KEPEGAWAIAN PENDIDIKAN DAN PELATIHAN KOTA MAGELANG (Jurnal Riset Mahasiswa, 2024)
ASN professionalism index is one way to approach the quality of ASN by using a composite index of several independent output indicators. In the preliminary study found problems related to the professionalism of the performance of ASN in the Education and Training Personnel Agency of Magelang City. to identify obstacles in increasing the professionalism of the performance of the State Civil Apparatus (ASN) in the Education and Training Personnel Board of Magelang City. This research is a qualitative research. The subjects in this study were 3 resource persons and the object of research was the professionalism of the performance of the State Civil Apparatus (ASN) in the Education and Training Personnel Agency of Magelang City. This study uses a qualitative analysis approach by describing, through interviews, observations, documentation and literature studies, with analysis using the concepts given by Miles and Huberman. The results of this study are the professionalism of the performance of the State Civil Apparatus (ASN) in the Education and Training Personnel Agency of Magelang City in fact assessed from several dimensions, namely qualifications, competence, performance and discipline. The results of the professional assessment of 38 ASN in the Education and Training Personnel Board of Magelang City still need to continue to make efforts to improve the professionalism of ASN, because the average ASN score is still very low, namely 53.42. Obstacles in improving the professionalism of the performance of the State Civil Apparatus (ASN) at the Education and Training Personnel Board of Magelang City are because the ASN positions are not entirely based on qualifications, competence and performance, the evaluation of staffing services has not been optimal, staff services have not fully utilized the development of information technology, lack of facilities and infrastructure. Infrastructure, lack of employee discipline, lack of ASN understanding of the provisions for preparing employee work targets. Efforts to improve the professionalism of the performance of the State Civil Apparatus (ASN) in the Education and Training Personnel Agency of Magelang City are (1) organizing and sending employees for learning tasks, training, socialization, technical guidance and the like as well as granting study permits; (2) Evaluation of the running of staffing services, (3) Improvement of facilities and infrastructure to support staffing services, (4) Implementation of reward and punishment system; and (5) Improved understanding of ASN regarding the renewal of personnel regulations.
Keywords: Professionalism; Performance; State Civil Apparatus (ASN)